2021
DOI: 10.1021/acsanm.1c02197
|View full text |Cite
|
Sign up to set email alerts
|

Doped Plasmonic Zinc Oxide Nanoparticles with Near-Infrared Absorption for Antitumor Activity

Abstract: Plasmonic nanoparticles (NPs) have been extensively investigated as active materials for application in the optoelectronics, photocatalysis, and electrochemistry fields. In particular, doped metal oxides have attracted significant interest because of their optical and electrical properties. In this study, we investigated the influence of aluminum, gallium, and indium on the doping process of zinc oxide (ZnO) NPs. Physicochemical characterization revealed that, upon doping, ZnO NPs exhibited enhanced optoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The combined effect of surface plasmon resonance and superparamagnetic properties of Fe 2 O 3 provides a multimodal platform for nano thermal ablation and MRI. Rissi et al 161 observed an interesting effect of doping zinc oxide NPs with aluminum, gallium, and indium on optoelectrical properties. The doping results in enhanced absorption in the near IR region and emission range in green-yellow, orange-red, and blue-violet, depending upon the doping element.…”
Section: Raman Probes For Theranosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined effect of surface plasmon resonance and superparamagnetic properties of Fe 2 O 3 provides a multimodal platform for nano thermal ablation and MRI. Rissi et al 161 observed an interesting effect of doping zinc oxide NPs with aluminum, gallium, and indium on optoelectrical properties. The doping results in enhanced absorption in the near IR region and emission range in green-yellow, orange-red, and blue-violet, depending upon the doping element.…”
Section: Raman Probes For Theranosticsmentioning
confidence: 99%
“…Only high doses (60-100 g/mL) of doped NPs revealed considerable toxicity after 24 hours of incubation. The potential of ZnO NPs for cell death in human tumors and healthy cell lines were also investigated in vitro 161 . Interestingly, ZnO NPs can stop the early leakage of medications under physiological circumstances 162 .…”
Section: Raman Probes For Theranosticsmentioning
confidence: 99%
“…As a kind of semiconducting fluorescent material, zinc oxide (ZnO) is low-toxic and biodegradable, showing promising potential in cell imaging and drug delivery. Eleftheriadou, Rissi, and Selim et al have tested the cytotoxicity of ZnO NPs, and the results demonstrated that ZnO NPs had little harmful effect on normal cells at suitable dose. Gwak et al have investigated the change in the physicochemical properties of ZnO nanoparticles under different pH conditions, and they claimed that the degradation of ZnO was significant in an acidic environment, while its dissolution was much slower under neutral and alkalescent conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Localized surface plasmon resonance (LSPR), which occurs in metal nanostructures, has attracted considerable attention from various optical-and electrical-based research fields, such as optical biosensors, color engineering, spectroscopy, metamaterials, and plasmonic optoelectronics [1][2][3][4][5]. Thus, large-scale, reproducible, high-throughput fabrication methods of wavelength-tunable LSPR substrates are in high demand not only for research but also for commercialization [6][7][8].…”
Section: Introductionmentioning
confidence: 99%